A Systematic Review of Intervention on Improving Cervical Cancer Screening Rates - Ida Maryati; Nur Rifa Fatmia; Okta Sri Rahmayani; Raden Roro Widiastuti; Lia Yulianti Yulianti; Reni Rohaniah; Rery Yuliani Pratiwi; Riana Hendra (International Journal of Nursing and Health Services (IJNHS), 2020)
Cervical cancer is a disease that can be prevented through early detection. However, cervical cancer is the fourth leading cause of death for women globally due to the low coverage of cervical cancer screening. An intervention is needed to increase the coverage of cervical cancer screening. This study aimed to provide current evidence of effective interventions to improve cervical cancer screening coverage, especially with low socio-economic conditions. This study uses a systematic design review to review the literature that has been evaluated in a structured, classified, and categorized based on evidence-based previously. The study's inclusion characteristics are as follows: all article searches are limited to those in English or Indonesian only, and scan bibliography to identify relevant articles, method design is RCT studies, or quasi-experiments. The study results found the characteristics of the article as follows: the majority of studies were conducted in the Americas, two studies in Asia, and one in Europe. The respondents' age varied from> 18 years to 75 years; the number of samples ranged from 102 to 12,061 respondents. Interventions were grouped into three types, namely: health education, self-testing, and reminders of the screening schedule. Among the three types of interventions most recommended is counseling with video media, because providing information with exciting media will increase knowledge which will increase women's interest in screening. Independent screening interventions can also increase the coverage of cervical cancer screening in women with low socio-economic conditions because this method allows more savings in funding